An unwanted guest - Lapeña, Shari, 1960- (Pamela Dorman Books, Viking, 2018)
"A weekend retreat at a cozy mountain lodge is supposed to be the perfect getaway. But when the storm hits, no one is getting away. It's winter in the Catskills and Mitchell's Inn, nestled deep in the woods, is the perfect setting for a relaxing maybe even romantic weekend away. It boasts spacious old rooms with huge woodburning fireplaces, a well-stocked wine cellar, and opportunities for cross-country skiing, snowshoeing, or just curling up with a good murder mystery. So when the weather takes a turn for the worse, and a blizzard cuts off the electricity and all contact with the outside world the guests settle in for the long haul. Soon, though, one of the guests turns up dead it looks like an accident. But when a second guest dies, they start to panic. Within the snowed-in paradise, something or someone is picking off the guests one by one. And there's nothing they can do but hunker down and hope they can survive the storm"--